2020
DOI: 10.1186/s13567-020-00766-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic modification of the protozoan Eimeria tenella using the CRISPR/Cas9 system

Abstract: Eimeria tenella has emerged as valuable model organism for studying the biology and immunology of protozoan parasites with the establishment of the reverse genetic manipulation platform. In this report, we described the application of CRISPR (clustered regularly interspaced short palindromic repeat)/Cas9 (endonuclease) system for efficient genetic editing in E. tenella, and showed that the CRISPR/Cas9 system mediates site-specific double-strand DNA breaks with a single guide RNA. Using this system, we successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…Now we have achieved transgenic E. acervulina with a fluorescent rate of more than 95% by using only fluorescent protein (EYFP) as a screening marker (Yu et al, unpublished data). At the same time, our laboratory has also achieved CRISPR/Cas9 gene knockout on Eimeria [ 36 , 37 ]. Therefore, after obtaining a stable transgenic E. acervulina line, we can use a gene-editing system to knock out the other selection markers like YFP, RFP, and DHFR-TS.…”
Section: Discussionmentioning
confidence: 99%
“…Now we have achieved transgenic E. acervulina with a fluorescent rate of more than 95% by using only fluorescent protein (EYFP) as a screening marker (Yu et al, unpublished data). At the same time, our laboratory has also achieved CRISPR/Cas9 gene knockout on Eimeria [ 36 , 37 ]. Therefore, after obtaining a stable transgenic E. acervulina line, we can use a gene-editing system to knock out the other selection markers like YFP, RFP, and DHFR-TS.…”
Section: Discussionmentioning
confidence: 99%
“…The programs EO100, EH100, and EO114 in Lonza 4D-Nucleofector have higher transfection efficiency than others ( Supplementary Figure S6 ). So far, there are two reported genome editing studies ( Hu et al, 2020 ; Tang et al, 2020 ). We summarized it as Supplementary Table S3 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been performed for optimization of the transgenic promoters, fluorescent reporter genes, fusion strategy, and selection for enrichment of positive transformants ( Clark et al, 2008 ; Hanig et al, 2012 ; Tang et al, 2016 ; Pastor-Fernandez et al, 2019 ), i.e., using the selection marker dihydrofolate reductase–thymidylate synthase ( DHFR ) gene ( Liu et al, 2008 ). Due to the lack of a method providing a continuous culture of Eimeria at one stage as Toxoplasma , no genome editing techniques have been reported until the past year ( Hu et al, 2020 ; Tang et al, 2020 ). It was reported that an E. tenella parasite strain harboring eCas9 expression would facilitate gene manipulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be needed to generate mutated versions of the Eimeria P4022-containing proteins targeting the P4022 sequence by genetically modifying Eimeria using the CRISPR/Cas9 system. [101] 2. RNAseq approach.…”
Section: Proposed Experiments To the Polyq/cxcr-type Receptor And The Lamina Propria Invasion Modelmentioning
confidence: 99%